PROSES PENYELESAIAN TINDAK PIDANA PENCURIAN RINGAN SECARA RESTORATIVE JUSTICE (Studi Kasus Kejaksaan Negeri Tanah Datar) - Husna, Nurul; Yustrisia, Lola; Munandar, Syaiful (PALAR (Pakuan Law review), 2024)
AbstractThe aim of the research is to explain the process of resolving petty theft crimes through restorative justice. The concept of restorative justice is a criticism of the concept of the criminal system which views crime as a violation of state regulations. The main problems are: What is the process for resolving petty theft crimes through restorative justice at the Tanah Datar District Prosecutor's Office, and what are the obstacles to the process of resolving petty theft crimes through restorative justice at the Tanah Datar District Prosecutor's Office and efforts to overcome the obstacles. The research method used in this research is an empirical juridical method. The conclusion, among other things, is that the legal regulations regarding minor crimes are basically regulated in the Criminal Code. even in Supreme Court Regulation (PERMA) Number 2 of 2012 concerning Adjustments to Limits for Minor Crimes and the amount of fines in the Criminal Procedure Code. Implementation of Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 Termination of Prosecution based on restorative justice. (case study at the Tanah Datar District Prosecutor's Office). Keywords: Restorative justice, Petty theft, Resolution of minor crimes, Prosecutor's office. AbstrakTujuan dari penelitian yaitu untuk menjelaskan bagaimana proses penyelesaian tindak pidana pencurian ringan melalui restorative justice Konsep keadilan restoratif adalah kritik terhadap konsep sistem pidana yang memandang kejahatan sebagai pelanggaran terhadap aturan Negara. Adapun masalah utama yaitu Bagaimana proses penyelesaian tindak pidana pencurian ringan melalui restorative justice di Kejaksaan Negeri Tanah Datar, dan Apa saja kendala pada proses penyelesaian tindak pidana pencurian ringan melalui restorative justice di Kejaksaan Negeri Tanah Datar dan upaya mengatasi kendala.  Metode penelitan yang digunakan dalam penelitian ini adalah metode yuridis empiris. Kesimpulan antara lain adalah bahwa pengaturan hukum tentang kejahatan ringan pada dasarnya telah diatur dalam KUHP. bahkan dalam Peraturan Mahkamah Agung (PERMA) Nomor 2 Tahun 2012 Tentang Penyesuaian Batasan Tindak pidana Ringan dan jumlah denda dalam KUHAP. Penerapan Peraturan Kejaksaan Republik Indonesia Nomor 15 Tahun 2020 Penghentian Penuntutan berdasarkan keadilan restorative. (studi kasus di Kejaksaan Negeri Tanah Datar). Kata Kunci : restorative justice, pencurian ringan, penyelesaian tindak pidana ringan, kejaksaan.